Unveiling the genomic landscape and adaptive mechanisms of the haloarchaeal genus Halogeometricum: spotlight on thiamine biosynthesis - Straková, Dáša; Sánchez-Porro, Cristina; de la Haba, Rafael R.; Ventosa, Antonio (Frontiers in Marine Science, 2024)
Recent advances in molecular and metagenomic analyses have enhanced the ability to precisely determine the microbiota of hypersaline environments of marine origin, such as solar salterns, saline lakes, and hypersaline soils, uncovering numerous yet-to-be-isolated prokaryotic groups. Our research focused on the hypersaline ecosystems within the Odiel Saltmarshes, a natural tidal wetland situated at the confluence of the Odiel and Tinto rivers in Huelva province, Southwestern Spain. Employing culture-dependent techniques, we aimed to isolate and characterize novel halophilic prokaryotes from this area. Two haloarchaeal strains, designated S1BR25-6T and S3BR25-2T were classified within the genus Halogeometricum based on Overall Genome Related Indexes (OGRIs) such as Orthologous Average Nucleotide Identity, digital DNA-DNA hybridization, and Average Amino Acid Identity as standard criteria for species delineation. Moreover, this study embarks on an exhaustive genome-based comparative analysis of the haloarchaeal genus Halogeometricum, delineating the metabolic capacities, osmoregulatory adaptations, and resistance to certain heavy metals of its species. The dual osmoregulatory mechanism observed by in-silico analysis of the Halogeometricum species combines “salt-in” and “salt-out” strategies which highlights the adaptive flexibility of these haloarchaea. In addition, capability for de novo thiamine biosynthesis of strain S1BR25-6T along with other Halogeometricum species underscores their metabolic complexity and resilience, offering insights into their role in ecosystem dynamics and potential biotechnological applications. Wet lab experimental analysis of strains S1BR25-6T and S3BR25-2T confirmed their resistance to heavy metals, particularly to arsenic, zinc, and cadmium, emphasizing their potential for bioremediation applications. Furthermore, conducting fragment recruitment analysis across different metagenomic datasets revealed a predominant recruitment of species from the genus Halogeometricum in hypersaline soils of Odiel Saltmarshes (especially the two novel strains), and in the brines of marine saltern ponds with high salt concentrations. These results contribute to a reinforced understanding of the extremely halophilic characteristics inherent to the genus Halogeometricum. Finally, taxogenomic analysis has substantiated that strains S1BR25-6T (= CCM 9250T = CECT 30624T), and S3BR25-2T (= CCM 9253T = CECT 30622T) denote two previously unidentified species within the genus Halogeometricum, for which we propose the names Halogeometricum salsisoli sp. nov., and Halogeometricum luteum sp. nov., respectively.